Unifocal Granuloma of Femur due to Langerhans' Cell Histiocytosis: A Case Report and Review of the Literature - Harpreet Singh; Satnam Kaur; P. Yuvarajan; Nishant Jain; Lalit Maini (Case Reports in Medicine)
The radiological diagnosis of osteolytic lesions of the long bones in pediatric population constitutes a challenge when the case history and clinical data are uncharacteristic. We believe that the description of few clinically and histologically proven cases to verify the existence of radiological signs useful for diagnosis may be of interest. Here, we describe a case of Langerhans' cell histiocytosis (LCH) presenting as unifocal eosinophilic granuloma of femur along with a brief review of the literature.